Contrasting ecological processes shape the Eucalyptus phyllosphere bacterial and fungal community assemblies - Zhen‐Zhen Yan; Qing‐Lin Chen; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Ji‐Zheng He; Hang‐Wei Hu (Journal of Sustainable Agriculture and Environment, 2022)
Abstract Introduction Phyllosphere microbiome is intrinsically linked to plant performance and ecosystem functioning. However, our knowledge about the role of ecological processes in shaping the biogeography of different phyllosphere microbial communities is scarce. Materials and Methods Here, we compared the biogeographic patterns of bacterial and fungal communities in phyllosphere samples of plants belonging to the genus of Eucalyptus of the Myrtaceae family collected from an over 4000 km transect. We investigated the relative importance of two major ecosystem processes (stochastic vs. deterministic) in shaping phyllosphere microbial community assemblies. Results Our results demonstrated that the neutral community model, which can quantify the degree of a community assembly determined by stochastic processes, explained 64.2% of the variations in bacterial community assembly, which had a normalized stochasticity ratio of 71.8%. These results suggest that the dominant role of stochastic processes in shaping bacterial community assembly. In contrast, phyllosphere fungal community assembly was mainly shaped by deterministic processes as revealed by a relatively small explanation rate of the neutral community model (48.7%) and a normalized stochasticity ratio of 25.1%. Variation partitioning analysis and random forest modelling results indicated that climatic factors, particularly mean annual precipitation and aridity index, were important in driving both bacterial and fungal biogeographic patterns in the phyllosphere. Edaphic factors, such as soil organic and mineral nitrogen content, were more closely related to fungal community assembly than to bacterial community assembly. The differential responses of bacterial and fungal communities to environmental factors could be attributed to the different traits of bacteria and fungi, that is, the higher potential dispersal rate and wider habitat niche of bacteria than fungi. Conclusion Our findings demonstrated that phyllosphere bacterial and fungal communities followed distinct community assembly processes, which is supported by the ‘size plasticity’ hypothesis that smaller organisms (bacteria) are less influenced by environmental conditions and are more homogeneous across space than larger organisms (fungi). These findings provide new insights into the microbial ecology of plant phyllosphere microbiomes.